Theory and practice to conserve freshwater biodiversity in the Anthropocene - Flitcroft, Rebecca; Cooperman, Michael S.; Harrison, Ian J.; Juffe‐Bignoli, Diego; Boon, Philip J. (Aquatic conservation, 2019)
The unprecedented impact of human activities on nature has led scientists to propose we might now be in a new geological epoch: the Anthropocene. Significant human alterations of freshwater systems include massive changes to soil erosion–deposition dynamics, hydrological regimes via impoundment and diversion, land‐use conversion, chemical and nutrient pollution, and human‐assisted range expansion of invasive species. In this human‐dominated epoch, biodiversity, which includes all life on Earth, is at risk, and freshwater biodiversity shows the strongest examples of the extent of this threat. We live in a world where it is necessary to find optimal ways to balance the growing human need for fresh water with ensuring that freshwater ecosystems remain functional in support of the biodiversity that inhabits them and the services these systems provide. Within the broader context of freshwater management in the Anthropocene, this special issue targets freshwater biodiversity and habitat conservation through a variety of lenses. Four main areas of emphasis include: conservation approaches; advances in model and tool development; enhancing water planning; and management and protection of species and habitats. For manuscripts included in this special issue, all authors were instructed to demonstrate how the material presented, be it commentary, conservation prioritization, new methodology or other subject matter, is broadly applicable and transferable.